If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(14.6)+11=0
We simplify the equation to the form, which is simple to understand
2(14.6)+11=0
Reorder the terms in parentheses
+(+29.2)+11=0
Remove unnecessary parentheses
+29.2+11=0
We move all terms containing to the left and all other terms to the right.
0=0-29.2-11
We simplify left and right side of the equation.
0=-40.2
0=-40.2
The left and right sides are not equal, therefore there is no solution. This equation is invalid.
| 8(-2x-4)=-52-12 | | 11+3x=38 | | 0.15x+0.05(8-x)=0.10(-12) | | x^2+169=7 | | .666n+6=18 | | 1.7t+8-1.62=.4t-.32+8 | | 0.6x-2=6+.25x | | 5x^2+24x-77= | | 3(14.6)+6= | | 2(y+2)+y=19-2(2y+3) | | Y=5+6y | | x-(-6)=15 | | .7n-15+n=2n-8-.4n | | 0.13y+0.09(y+9000)=1690 | | .75n+2=3 | | 3x+6+2x+11=90 | | .7n-15+n=2n-.4n | | X+(x+3)=49 | | 3n-2= | | 4.1x=9.5x+23.7 | | -10x+3+3x^2= | | 12(v+4)-4v=2(4v+4)-10 | | -4x^3+36x^2-56x= | | 80=2x^2-5x | | 5x+17=90 | | 2g^2+11gh+15h^2=0 | | -(1+7x)-6(-6-x)=36 | | (7-v)(4v-6)=0 | | -4y=6y+9 | | 0.22(x-4)+0.33(x+3)=4 | | 9x+4+3x+2=-30 | | 2x^2-27x+25=0 |